Carceral citizenship in post-protest Nicaragua: Political imprisonment and civil death - Weegels, Julienne (European Review of Latin American and Caribbean Studies, 2023)
This paper demonstrates how the extension and intensification of penal power across Nicaragua following the 2018 protests has produced particular experiences of carceral citizenship. In order to fully understand these experiences, it is necessary to take into account that states can enforce carceral citizenship (and its restrictions, benefits, and duties) not only legally, but also extralegally. As such, I examine the tenets of carceral citizenship in relation to the country’s hybrid carceral system, conceptualizing how such citizenship may be produced and policed. Following from this, I elicit how political prisoners are acted upon by (para)state actors and excluded from prison’s co-governance arrangements, which pushes some of them to engage in (dis)organizing practices of their own. Following them into their post-release lives, I examine the tight ‘transcarceral grip’ they are subjected to. This produces a state of de facto civil disenfranchisement, understood by excarcelados as “civil death.” In spite of their predicament, however, released political prisoners continue to organize in the face of the Sistema and the violations it has committed (and continues to commit). Resumen: Encarcelamiento político reduz en Nicaragua: Ciudadanía carcelaria conflictiva Este artículo demuestra cómo la extensión e intensificación del poder penal en Nicaragua tras las protestas de 2018 ha producido experiencias particulares de ciudadanía carcelaria. A fin de comprender plenamente estas experiencias, es necesario tener en cuenta que los estados pueden hacer cumplir la ciudadanía carcelaria (y sus restricciones, beneficios y deberes) no sólo legal, sino también extralegalmente. Por ello, examino los principios de la ciudadanía carcelaria en relación con el sistema carcelario híbrido del país, conceptualizando cómo se puede producir y vigilar dicha ciudadanía. A partir de ahí, explico cómo los actores (para)estatales actúan sobre los presos políticos y los excluyen de los acuerdos de cogobierno de las prisiones, lo que empuja a algunos de ellos a participar en sus propias prácticas de (des)organización. Siguiéndoles en su vida posterior a la puesta en libertad, examino el estrecho “control transcarcelario” al que están sometidos. Esto produce un estado de privación de derechos civiles de facto, entendido por los excarcelados como “muerte civil”. Sin embargo, a pesar de su difícil situación, los presos políticos excarcelados siguen organizándose frente al Sistema y las violaciones que ha cometido (y sigue cometiendo).